2013
DOI: 10.1186/1475-9276-12-69
|View full text |Cite
|
Sign up to set email alerts
|

The influence of socio-economic status and multimorbidity patterns on healthcare costs: a six-year follow-up under a universal healthcare system

Abstract: IntroductionMultimorbidity has been linked to elevated healthcare utilization and previous studies have found that socioeconomic status is an important factor associated with multimorbidity. Nonetheless, little is known regarding the impact of multimorbidity and socioeconomic status on healthcare costs and whether inequities in healthcare exist between socioeconomic classes within a universal healthcare system.MethodsThis longitudinal study employed the claims database of the National Health Insurance of Taiwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 33 publications
4
47
3
Order By: Relevance
“…States [23,24,3,[25][26][27][28][29][30][31][32][33][34], seven in Europe [13,[35][36][37][38][39][40], t wo in Australia [41], one each fro m Canada [42], Singapore 3 [43] and Taiwan [44], and two in middle -or low-inco me regions [40,45]. Overall, twenty studies used a prevalence 4 approach [23, 24, 3, 25-28, 13, 35, 30, 31, 41, 37, 38, 45, 39, 46, 40, 32, 43], seven used an incidence approach [36, 5 29, 44, 42, 33, 34, 27], and only one used an economic model to estimate the lifet ime costs of mult imorb idity [36].…”
mentioning
confidence: 99%
“…States [23,24,3,[25][26][27][28][29][30][31][32][33][34], seven in Europe [13,[35][36][37][38][39][40], t wo in Australia [41], one each fro m Canada [42], Singapore 3 [43] and Taiwan [44], and two in middle -or low-inco me regions [40,45]. Overall, twenty studies used a prevalence 4 approach [23, 24, 3, 25-28, 13, 35, 30, 31, 41, 37, 38, 45, 39, 46, 40, 32, 43], seven used an incidence approach [36, 5 29, 44, 42, 33, 34, 27], and only one used an economic model to estimate the lifet ime costs of mult imorb idity [36].…”
mentioning
confidence: 99%
“…Other studies that are not included in the present review have also demonstrated that socio-economic status has an impact on both prevalence rates and healthcare utilization rates [10] [43] [44]. Kuo and Lai [44] found that cases of patients with multimorbidity varied according to socio-economic status and demographic characteristics.…”
Section: Discussionmentioning
confidence: 87%
“…But from a broader point of view, there are various other factors affecting both said readiness and the healthcare fees they might be willing pay, such as: health insurance, family/personal income, job status, gender, health status, education, personal medical knowledge, etc [26][27][28]. Those who work in the medical/healthcare sector, who have ©2016 Vuong QH, Vu QH 4 above-average income, or who are civil servants, are more likely to participate in periodic health examinations; and, being ready for higher payments, their health status are generally better [27][28][29][30]. On the contrary, below-average-income citizens have restricted access to healthcare services and are less likely to take particular medical checks such as periodic GHE [27][28][29]31].…”
Section: Introductionmentioning
confidence: 99%
“…Those who work in the medical/healthcare sector, who have ©2016 Vuong QH, Vu QH 4 above-average income, or who are civil servants, are more likely to participate in periodic health examinations; and, being ready for higher payments, their health status are generally better [27][28][29][30]. On the contrary, below-average-income citizens have restricted access to healthcare services and are less likely to take particular medical checks such as periodic GHE [27][28][29]31]. Also, females tend to take regular physical examinations more than males due to their general self-care tendencies and their specific physiological attributes [12,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation